Medical Office Automation Integrated into the Distributed Architecture of a Hospital Information System - Scherrer, J.-R.; Revillard, C.; Borst, F.; Berthoud, M.; Lovis, C. (Methods of Information in Medicine, 1994)
Patient histories, discharge summaries, and medical consultant reports are made up of written texts. Therefore, the gathering and archiving of these texts in machine-readable form has many characteristics of computer-based medical records. In Geneva, approximately 1,540 PCs are connected to the Hospital Information System DIOGENE 2, with the possibility of accessing all the functions offered by the system without losing any of their MS-DOS word processing capabilities. The UNIDOC system, presented in this paper, takes all these features into account, a real marriage of technologies between the MS-DOS environment and the distributed client-server architecture. The INGRES database management system supports the entire archiving process of the medical patient texts, structured by prelabelled paragraphs and automatically indexed. Both the quality and accessibility of the records are enhanced, while the archiving capacity is neither too limited nor too expensive.
Keywords: Computer-Based Medical Records; Client-Server Architecture; Medical Archives; Medical Office Automation; Hospital Information Systems